Socialization and Legal Assistance on Intellectual Property Rights: A Risk Mitigation Strategy for MSMEs in West Aceh through Trademark Protection - Effida, Dara Quthni; Kemalasari, Putri; Yuana, Adella (Faculty of Law, Universitas Pattimura, 2025)
Introduction: West Aceh Regency in 2025 recorded a total of 2,011 MSMEs. However, not all of them have utilized intellectual property rights, particularly trademarks, which could provide legal protection for these businesses. Based on this condition, the implementation of this community engagement initiative is considered highly important to provide legal protection for MSMEs in West Aceh.Purposes of The Devotion: The purpose of this article is to provide outreach and legal assistance on intellectual property as a risk mitigation strategy for MSMEs in West Aceh through trademark protection. Method of The Devotion: The method of community engagement includes risk mitigation outreach through trademark legal protection, training on completing trademark registration forms, assistance with the registration process, and the application of technology through online consultations to monitor the progress of submitted trademark registrations.Results Main Findings of the Devotion: The results of the community engagement program indicate a significant increase in participants' understanding of trademark rights. Prior to the outreach activity, only 15% of participants were aware of the trademark registration procedures; following the program, this figure rose to 90%. The main obstacles identified include limited financial resources, similarity in brand names, lack of legal information and literacy, and restricted access to legal services. The post-activity improvement in legal awareness demonstrates that this community engagement initiative has had a positive impact on the legal consciousness of MSME actors.